Development and parametric study of a 1kW class free-piston stirling cryocooler (FPSC) driven by a dual opposed linear compressor for LNG (Re)liquefaction. (August 2019) - Park, Jiho; In, Sehwan; Ko, Junseok; Kim, Hyobong; Hong, Yongju; Yeom, Hankil; Park, Seongje
Highlights: Developed free-piston stirling cryocooler (FPSC) and tested for LNG (re)liquefaction. Developed numerical model that reflects a damping effect on the displacer. Explained dynamics of the piston and displacer using a phasor diagram. Classified mechanical and thermal losses of the FPSC. Abstract: This research paper discusses the free-piston Stirling cryocooler (FPSC) in conjunction with a dual-opposed linear compressor. The system was tested under various operational conditions. The developed compressor can produce mass flow with an efficiency exceeding 60%; a loss analysis was conducted with care. The dynamic and thermal aspects of the experimental results are extensively verified via the numerical model. The model describes the physical characteristics of the Stirling cryocooler when a damping effect is applied to the displacer. The damping effect incorporated in the model is expressed through a function of the expansion work at the cold-end. It was also confirmed that the damped motion of the displacer is more suitable than undamped motions for describing real situations. The relevant dynamic characteristics of the piston and the displacer are also explained through the introduction of a phasor diagram. The developed model explains the physics of the Stirling cryocooler well, while accurately explaining the quantity of losses (i.e. heat conduction, imperfection of regenerator and shuttle heat transfer) that are distributed at its cold-end. The thermal load is regulated at various cold-end temperatures of 110 K, 120 K, 150 K and 190 K, and the system is capable of exerting maximum Carnot efficiencies of 25%, 27%, 28% and 29%, respectively.